Antiproliferative evaluation of various aminoquinoline derivatives - Zorc Branka; Rajić Zrinka; Perković Ivana (Acta Pharmaceutica)
Four classes of aminoquinoline derivatives were prepared: primaquine ureas 1a–f, primaquine bis-ureas 2a–f, chloroquine fumardiamides 3a–f and mefloquine fumardiamides 4a–f. Their antiproliferative activities against breast adeno-carcinoma (MCF-7), lung carcinoma (H460) and colon carcinoma (HCT 116 and SW620) cell lines were evaluated in vitro, using MTT cell proliferation assay. The results revealed a low activity of primaquine urea and bis-urea derivatives and high activity of all fumardiamides, with IC50 values in low micromolar range against all tested cancer cell lines.